2008
DOI: 10.1108/13522750810864422
|View full text |Cite
|
Sign up to set email alerts
|

Small versus big stories in framing consumption experiences

Abstract: PurposeThe purpose of this paper is to highlight the importance and utility of introspective accounts to ethnography when it deals with consumption experiences.Design/methodology/approachThe paper reviews the changes in the way “reflexive consumers” write introspective narratives about their intimate thoughts and deep feelings lived during an experience and takes advantage of previous research carried out in different contexts, e.g. music concerts and internet‐based services.FindingsThe paper specifies the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 20 publications
2
67
0
7
Order By: Relevance
“…Diary research has found some uptake in consumer research to date for issues such as examining how people consume chocolate (Zarantonello and Luomala, 2011), experience surfing weekends or a classical music concert (Caru and Cova, 2008), and how students live their daily lives (Patterson, 2005). Perhaps unsurprisingly, there has recently been an increase in electronic forms of data collection, such as using the Internet and PDAs (Personal Digital Assistants).…”
Section: Methodsmentioning
confidence: 99%
“…Diary research has found some uptake in consumer research to date for issues such as examining how people consume chocolate (Zarantonello and Luomala, 2011), experience surfing weekends or a classical music concert (Caru and Cova, 2008), and how students live their daily lives (Patterson, 2005). Perhaps unsurprisingly, there has recently been an increase in electronic forms of data collection, such as using the Internet and PDAs (Personal Digital Assistants).…”
Section: Methodsmentioning
confidence: 99%
“…Contudo, nos estudos relacionados ao consumo, ainda são incipientes no Brasil os trabalhos que lançam mão de alguma abordagem da análise do discurso, certamente, pela tendên-cia, reinante nesse campo, de seguir uma linha mais quantitativa como estratégia de pesquisa LArA, 2008). Na literatura internacional é possível encontrar alguns trabalhos na área que utilizam a análise do discurso para interpretar experiências de consumo (SITZ, 2008;CArÙ;COVA, 2008).…”
Section: Técnica Projetivaunclassified
“…Experiential marketing has become a cornerstone of many recent advances in areas such as retailing, branding and events marketing, and it is crossing over to the service sector, from hotels to restaurants to airlines (Smith and Wheeler, 2002) with enthusiasts reported in all sectors of the global economy from consumer products to health care providers (Williams, 2006). Therefore, understanding consumption experience has become a prime goal of today's marketers, especially with the rise of experiential marketing approaches (Caru and Cova, 2008) that seek to capture customers' whole minds, to evoke positive emotions and to render them captivated (Shaw, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The rise of experiential marketing during last decade (Pine and Gilmore, 1999;Schmitt, 1999Schmitt, , 2003 has turned the understanding of consumption experiences into a hot topic for market researchers (Caru and Cova, 2008). Experiential marketing has become a cornerstone of many recent advances in areas such as retailing, branding and events marketing, and it is crossing over to the service sector, from hotels to restaurants to airlines (Smith and Wheeler, 2002) with enthusiasts reported in all sectors of the global economy from consumer products to health care providers (Williams, 2006).…”
Section: Introductionmentioning
confidence: 99%